Building a rationale diagram for evaluating user story sets - Wautelet, Yves; Heng, Samedi; Kolp, Manuel; Mirbel, Isabelle; Poelmans, Stephan (2016 IEEE Tenth International Conference on Research Challenges in Information Science (RCIS), 2016)
Requirements representation in agile methods is often done on the basis of User Stories (US) which are short sentences relating a WHO, WHAT and (possibly) WHY dimension. They are by nature very operational and simple to understand thus very efficient. Previous research allowed to build a unified model for US templates associating semantics to a set of keywords based on templates collected over the web and scientific literature. Since the semantic associated to these keywords is mostly issued of the i* framework we overview in this paper how to build a custom rationale diagram on the basis of a US set tagged using that unified template. The rationale diagram is strictly speaking not an i* strategic rationale diagram but uses parts of its constructs and visual notation to build various trees of relating US elements in a single project. Indeed, the benefits of editing such a rationale diagram is to identify depending US, identifying EPIC ones and group them around common Themes. The paper shows the feasibility of building the rationale diagram, then points to the use of these consistent sets of US for iteration content planning. To ensure the US set and the rationale diagram constitute a consistent and not concurrent whole, an integrated Computer-Aided Software Engineering (CASE) tool supports the approach.